Morphological modularity in the anthropoid axial skeleton. Issue 172 (November 2022) - Jung, Hyunwoo; von Cramon-Taubadel, Noreen
Abstract: Previous research has found that hominoids have stronger modularity between limb elements than other anthropoids, suggesting that there is less constraint on morphological diversification (e.g., limb proportions) in hominoids in terms of evolutionary independence. However, degrees of modularity in the axial skeleton have not been investigated across a broad range of anthropoid taxa. Thus, it is unknown whether hominoids also have stronger modularity in the axial skeleton than other anthropoids, which has implications for the evolution of diverse torso morphologies in Miocene apes as well as the evolution of novel characteristics in the skull and vertebrae of fossil hominins. In this study, 12 anthropoid genera were sampled to examine degrees of modularity between axial skeletal elements (i.e., cranium, mandible, vertebrae, and sacrum). Covariance ratio coefficients were calculated using variance/covariance matrices of interlandmark distances for each axial skeletal element to evaluate degrees of modularity. The results showed that Alouatta, Hylobates, Gorilla, Pan, and Homo showed generally stronger modularity than other anthropoid taxa when considering all axial skeletal elements. When only considering the vertebral elements (i.e., vertebrae and sacrum), Alouatta, Hylobates, Gorilla, and Pan showed generally stronger modularity than other anthropoid taxa. Humans showed stronger modularity between the skull and vertebrae than other hominoids. Thus, the evolution of novel characteristics in the skull and vertebral column may have been less constrained in fossil hominins due to the dissociation of trait covariation between axial skeletal elements in hominoid ancestors, thus fostering more evolutionary independence between the skull and vertebral column.